“Going into the black box”: a policy analysis of how the World Health Organization uses evidence to inform guideline recommendations - Ingold, Heather; Gomez, Gabriela B.; Stuckler, David; Vassall, Anna; Gafos, Mitzy (Frontiers in Public Health, 2024)
Background The World Health Organization (WHO) plays a crucial role in producing global guidelines. In response to previous criticism, WHO has made efforts to enhance the process of guideline development, aiming for greater systematicity and transparency. However, it remains unclear whether these changes have effectively addressed these earlier critiques. This paper examines the policy process employed by WHO to inform guideline recommendations, using the update of the WHO Consolidated HIV Testing Services (HTS) Guidelines as a case study. Methods We observed guideline development meetings and conducted semi-structured interviews with key participants involved in the WHO guideline-making process. The interviews were recorded, transcribed, and analysed thematically. The data were deductively coded and analysed in line with the main themes from a published conceptual framework for context-based evidence-based decision making: introduction, interpretation, and application of evidence. Results The HTS guideline update was characterized by an inclusive and transparent process, involving a wide range of stakeholders. However, it was noted that not all stakeholders could participate equally due to gaps in training and preparation, particularly regarding the complexity of the Grading Recommendations Assessment Development Evaluation (GRADE) framework. We also found that WHO does not set priorities for which or how many guidelines should be produced each year and does not systematically evaluate the implementation of their recommendations. Our interviews revealed disconnects in the evidence synthesis process, starting from the development of systematic review protocols. While GRADE prioritizes evidence from RCTs, the Guideline Development Group (GDG) heavily emphasized “other” GRADE domains for which little or no evidence was available from the systematic reviews. As a result, expert judgements and opinions played a role in making recommendations. Finally, the role of donors and their presence as observers during GDG meetings was not clearly defined. Conclusion We found a need for a different approach to evidence synthesis due to the diverse range of global guidelines produced by WHO. Ideally, the evidence synthesis should be broad enough to capture evidence from different types of studies for all domains in the GRADE framework. Greater structure is required in formulating GDGs and clarifying the role of donors through the process.